VD_FINDINFO Jug / 2016 / 410 vom 26. November 2013 - VD Tribunal cantonal (2013)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉVISIONDÉCISION, MOTIF DE RÉVISION, EXPERTISE PSYCHIATRIQUE | 410 al. 1 let. a CPP (CH), 413 al. 2 CPP (CH)